Assessment of Language Impairment Management of Post Stroke at Erbil Public Hospitals - Azad Hassan Kheder; Najat Muhammed Amin Mawlood (Diyala Journal of Medicine, 2024)
Background: Stroke is the most common cause of aphasia which need to be managed because it postpones stroke recovery and causes psychological and social problems for the patients and their families. Researchers have observed that the issue of language disorder in post-stroke patients has been poorly addressed in Kurdistan Region. Objective: This neurolinguistic study aims at presenting a comprehensive scale study about the demography of stroke and aphasic patients at Rizgary hospital over a period of TWO months in2024. Patients and Methods: This cross-sectional study is carried out at Rizgary Public hospital in Erbil-Kurdistan Region. Demographic for all the patients who were registered at Erbil hospitals during the TWO months in 2024. Then the process of diagnosing aphasia and dysarthria as language impairments are carried out. Results: Among 234 subjects, the mean age of post stroke patients is 33.4 ± 22.038001years .15.3% of patients were not paralyzed, meanwhile 44.8% got right side body paralysis, followed by left side 38%, and both side 1.7%. The highest risk factor is Hypertension (68.8%), followed by Diabetes mellitus (41.4%), and Ischemic heart disease (21.7%). Conclusion: Language disorders is about (71.4%) which is a high range among post-stroke patients. Language disorders does not only affect stroke management but it also impair the individual’s quality of life. If language impairments are screened earlier in patients, it is possible to intervene in language skills and work through speech therapy. Keywords: Language impairment, stroke, dysarthria.